2014
DOI: 10.1590/2317-1545v36n3919
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pod permeability and seed quality in soybean

Abstract: -The aim of this study was to evaluate the influence of pod wall permeability on the physiological quality of soybean seed. The cultivars studied were Sant'Ana, FT-2, FT-10, Bossier, Davis and the breeding line F 84-7-30, with a black seed coat. Pods were collected from plants at the R4, R5, R6, R7 and R8 development stages, which composed the treatments in regard to time of harvest. The parameters of permeability and the lignin content of the pods and the seeds within the pods were evaluated. The seeds were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…Growing trend of electrical conductivity of seeds with delay in harvest and with decrease in moisture content of seeds after physiological maturity, it indicates that seed possess highest vigour at physiological maturity (H 1 ) afterward it goes on decreasing. Similar results were reported by Gris andPinho (2011), Hampton et al, (1992), Marcos-Filho et al, (1994) and Oliveira et al, (2014).…”
Section: Electrical Conductivity Of Seedsupporting
confidence: 91%
“…Growing trend of electrical conductivity of seeds with delay in harvest and with decrease in moisture content of seeds after physiological maturity, it indicates that seed possess highest vigour at physiological maturity (H 1 ) afterward it goes on decreasing. Similar results were reported by Gris andPinho (2011), Hampton et al, (1992), Marcos-Filho et al, (1994) and Oliveira et al, (2014).…”
Section: Electrical Conductivity Of Seedsupporting
confidence: 91%
“…The high lignin content in seeds tegument make it difficult the process of water absorption and favor the loss of important substances, affecting the electrical conductivity values (Oliveira et al, 2014). In this study, seeds of the cultivar BRS Valiosa RR, which have high lignin content, showed greater vigor when the plants were desiccated.…”
Section: Resultsmentioning
confidence: 62%
“…Studying the influence of lignin content in the quality and viability of soybean seeds after storing, Dantas et al (2012) observed that cultivars with higher lignin content showed lower proportion of normal seedling. Oliveira et al (2014) discuss that seeds with higher lignin content absorb less water, which is essential to the metabolic activities that occur during the germination process. In this study, the desiccant Finale® 1/ Times of application of desiccants: 1 st time = 50% seeds water content, 2 nd time = 40% seeds water content, and 3 rd time = 30% seeds water content.…”
Section: Resultsmentioning
confidence: 99%
“…Lignin is a major factor influencing seed quality, including germination, shattering, hard-seed, water permeability, and resistance to seed deterioration. For example, de Oliveira et al ( 2014 ) concluded that higher lignin content in the pod and in the seeds may contribute to the decrease in seed deterioration from moisture. Alvarez et al ( 1997 ) observed similar results among the cultivars, with the greatest lignin content in the seed coat for the seeds of the soybean cultivars.…”
Section: Introductionmentioning
confidence: 99%